Alice’n Records / Adam Badruddin Syah - Adam, Badruddin Syah (2020)
Alice’n Records is a sole proprietorship record company owned by musician Adam Badruddin Syah. They are an independent record label based in Malaysia and have two branches, one in Gombak and the other in Ampang. A successful and recognizable musician, Adam Badruddin Syah has huge models to start up a record company. He founded Alice’n Records in his hometown of Gombak, Selangor where he purchased a building a refurbished building for his personal recording studio but in the end thought of the idea to start up a record label. The business began its retail operation in Gombak, Selangor thus making it the record label’s headquareters. The other store of Alice’n Records is located in Ampang which also has a record pressing plant where they produce vinyl records making the first ever company in Malaysia to press vinyl records. The name Alice’n Records derives from Adam Badruddin Syah’s wife’s name as she is an avid record collector and admirer of vintage music gear. The company does not only sell vinyl records but also does other services such as studio recording for artists and also restoring old and broken phonographs or record players. Many famous bands have signed under Alice’n Records’ label such as “Bunkface” of Malaysia and also The Raconteurs which is a highly acclaimed rock band from the United States. Adam Badruddin Syah’s admiration has also led him to do other projects with the record company. For example, Alice’n Records once reissued lost tracks of old delta blues musicians such as Robert Johnson, Blind Lemon Jefferson, Big Bill Broonzy and much more from Paramount Records, one of the oldest record labels from the United States. They collaborated with another major independent record label from the UK known as 4AD for this project. This project led the two record companies to be nominated for Grammy’s for best box-set and packaging, the first ever record company in Malaysia to achieve this nomination. The aim for Adam Badruddin Syah whilst starting the company is to share his love of music with all people and expose new and maybe young and upcoming artists to appreciate old music. Adam Badruddin Syah has a keen liking for analog machinery as he believes that it highly under-appreciated these days. So, he wants to let people know and understand the struggle and hardmanship that musicians had to face during the times of analog recording before digital technology came out.